Pelatihan Pembuatan Bahan Ajar Berbasis Kearifan Lokal di Sekolah Dasar - Hasnah Faizah; Mangatur Sinaga; Charlina Charlina; Yanti Yandri Kusuma; M Imam Arifandy (CANANG: Jurnal Pengabdian Masyarakat, 2023)
Lack of teacher experience in making teaching materials based on local wisdom is one of the problems that arises at SDN 004 Pulau, SDN 009 Pulau, SDN 001 Pulau, SDN 005 Pulau, SDN 003 Muara Uwai, SDN 019 Muara Uwai, this is due to the teachers who teach in This school is a new graduate from the PGSD study program at Pahlawan University. Although in theory the teachers at the elementary school do not master educational science. In the learning process, teachers are less careful in making teaching materials based on local wisdom and still lack understanding about the proper and correct preparation of teaching materials, so there is a need for students' physical creativity which has not been facilitated by teachers. A solution must be immediately sought to find a solution for teachers to make teaching materials physically and mentally balanced. Increasing teachers' abilities through training is very important, but the SDNs mentioned above are still having problems in bringing in education experts to provide training. Based on these conditions, to be able to improve teachers' professional abilities in making teaching materials for elementary school teachers in elementary schools through training so that teachers gain direct experience in using good and correct teaching materials so that effective learning occurs.